Communities of the Converted : Ukrainians and Global Evangelism - Wanner, Catherine (Book collections on Project MUSE., 2007)
In revealing the phenomenal transformation of religious life in a land once thought to be militantly godless, Wanner shows how formerly socialist countries experience evangelical revival. She engages issues of migration, morality, secularization, and global evangelism, while highlighting how they have been shaped by postsocialism.